On desperate ground the Marines at the reservoir, the Korean War's greatest battle - Sides, Hampton (Doubleday, 2018)
"A chronicle of the extraordinary feats of heroism by Marines called on to do the impossible during the greatest battle of the Korean War."--Provided by publisher.